Immunological mutational signature in adenosquamous cancer of pancreas: an exploratory study of potentially therapeutic targets. (4th May 2018) - Silvestris, Nicola; Brunetti, Oronzo; Pinto, Rosamaria; Petriella, Daniela; Argentiero, Antonella; Fucci, Livia; Tommasi, Stefania; Danza, Katia; De Summa, Simona
ABSTRACT: Objectives : Adenosquamous cancer of pancreas (ASCP) is a rare variant of pancreatic adenocarcinoma (PDAC). It is characterized by poor prognosis and lacks of literature data supporting the choice of systemic therapies. The role of immunotherapy for this malignancy is still unknown. In this study, we evaluated any differences between immune-related genes of PDAC and its adenosquamous variant with the aim to characterize these histothistotypes and eventually identify potential biomarkers useful for an immune-therapy approach in ASCP. Methods : We compared the mutational status of a customized gene panel, including 41 genes involved in immunity checkpoint, inflammation and control of leukocytes, B and T cells proliferation of PDAC and ASCP. Moreover, we evaluated the immunohistochemical expression of programmed death ligand 1 (PD-L1). Results : We observed a status of 'hypermutation' of genes included in our panel in ASCP (22/41 mutated genes). Furtheremore, PD-L1 was found to be expressed in about 15% of the squamous component of ASCP tissue. Conclusion : Due to genetic characteristics and to PD-L1 expression in ASCP compared to PDAC tissue, we can conclude that ASCP presents a potential sensitivity to immunological therapy.